Сучасні аспекти діагностики та лікування вузлових форм зоба - Коваленко, А. Є.; Болгов, М. Ю.; Таращенко, Ю. М. (Clinical Endocrinology and Endocrine Surgery, 2009)
Based on materials from the Institute’s Surgical Clinic the authors have conducted an analysis of treatment of 5023 patients with thyroid nodules. An optimal therapeutical program includes modern methods of ultrasound, hormonal, cytological, radio- and X-ray diagnosis, which allows to verify morphologic features of thyroid nodules before operation, determine indications and size of surgery. It has been noted that introduction of ultrasound and cytological diagnosis allows to an objective assessment of oncological risk of primarily diagnosed focal thyroid neoplasms and reduce the number of operations performed for thyroid nodules. The authors note a tendency to an increase in operation volume within thyroidectomy in multinodular goiter, autoimmunne disease, nodular toxic goiter.